Pewarisan Tari Ngagah Harimau Desa Pulau Tengah Kecamatan Keliling Danau Kabupaten Kerinci - Annisa Marvelia; Afifah Asriati (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study aims to determine and describe the inheritance of Tiger Ngagah Dance in Pulau Tengah Village, Keliling Danau District, Kerinci Regency. This type of research is qualitative research with a descriptive approach to analysis. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery, cameras and flash drives. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusions. The results showed that the inheritance form of the Tiger Ngagah Dance, Central Island Village, Keliling Danau District, Kerinci Regency uses a closed inheritance system. The closed inheritance system can be done based on lineage, kinship, and community or group, or based on clan or tribe. In addition, closed inheritance can also be validated in the similarity of regional identity or villages and villages. The purpose of the closed system is that those who can inherit the dance must be based on the lineage of the previous heir or must be from the line of descent from the heir who will hand over the inheritance of the Tiger Ngagah dance.